ANALISIS TRANSMISI KEBIJAKAN MONETER JALUR EKSPEKTASI DALAM MEMPENGARUHI INFLASI DI INDONESIA - Muhammad Rasyad Gunawan; Mike Triani (Universitas Negeri Padang, 2025)
This study aims to analyzes the monetary policy transmission mechanism through the expectations channel in influencing inflation in Indonesia, based on the premise that uncontrolled inflation can erode purchasing power, hinder investment, and slow economic growth. The study employs quarterly secondary data for the 2006–2023 period obtained from the Economic and Financial Statistics of Indonesia (SEKI) and the Central Bureau of Statistics (BPS), covering the policy interest rate (BI-Rate), inflation expectations, exchange rate, Gross Domestic Product (GDP), and inflation. The analytical method used is the Vector Error Correction Model (VECM), preceded by the Augmented Dickey-Fuller (ADF) stationarity test, optimal lag selection, Johansen cointegration test, Granger causality test, and Impulse Response Function (IRF) analysis. The results indicate that all variables are non-stationary at level but become stationary at first difference, and a long-run cointegration relationship exists, validating the application of VECM. In the long run, the BI-Rate, inflation expectations, and exchange rate significantly affect inflation, while GDP is insignificant. In the short run, a bidirectional causal relationship is found between the exchange rate and inflation expectations. The IRF analysis reveals that monetary policy shocks influence inflation with a certain time lag. The study concludes that policy credibility and effective communication are crucial in strengthening the effectiveness of the expectations channel in controlling inflation. It is recommended that Bank Indonesia enhance policy transparency and public economic literacy to strengthen public confidence in achieving inflation targets.Keywords: Monetary Policy Transmission, Inflation Expectations, Exchange Rate, GDP, Inflation, VECM